Expression of the bcl-2 protein in B cell lymphomas arising from mucosa associated lymphoid tissue. Issue 1 (January 1995) - Navratil, E; Gaulard, P; Kanavaros, P; Audouin, J; Bougaran, J; Martin, N; Diebold, J; Mason, D Y
Abstract : AIM--To determine whether lymphomas arising from mucosa associated lymphoid tissue (MALT) express the bcl-2 protein. METHODS--Forty two cases of MALT B cell lymphomas, 20 low grade neoplasms and 22 high grade tumours, were studied. Immunohistological staining was performed on paraffin wax embedded tissue using a monoclonal antibody specific for the bcl-2 protein. RESULTS--All of the low grade lymphomas gave positive results on staining, with clear cytoplasmic labelling for bcl-2 protein in the small neoplastic cells, some of which formed characteristic lympho-epithelial lesions. A striking feature was that larger bcl-2 negative cells were observed in nine of these tumours. They were either scattered singly among the small neoplastic cells or formed small clusters, suggesting that they could represent early areas of transformation to high grade neoplasia. Germinal centres in the vicinity of the tumours lacked bcl-2 protein and hence contrasted clearly with the neoplastic cells. In some cases this permitted germinal centres, which were not obvious on conventional histological staining, to be recognised. In 20 of the 22 cases of high grade B cell lymphoma the large neoplastic cells were bcl-2 negative; the remaining two cases, however, contained a proportion of large neoplastic bcl-2 positive cells. In four of the 22 cases of high grade tumours a low grade component was found which expressed bcl-2 in all cases. CONCLUSION--Bcl-2 protein is expressed in low grade, but not in most high grade, MALT lymphomas. In view of recent data indicating that most high grade nodal lymphomas express bcl-2, these findings suggest that MALT lymphomas may regulate bcl-2 gene expression differently to nodal lymphomas.